History and gender: lines of research and recent debates in Europe and North America - Blasco Herranz, Inmaculada (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this article is to present a characterization of the current situation of the history of gender, (mainly considering European and North American productions) in which the most relevant lines of research developed in the last 15 years are collected, as well as to briefly point out some of the main controversies that have recently arisen. Its theoretical dynamism (always in connection with feminist theories) has been translated into growth and expansion based on the confluence with fields of investigation such as the history of masculinities, of sexuality/ies, or of postcolonial history. In this way, we can see a broadening of the field of study which, together with the impact of the cultural processes linked to globalization, results in a production that is not only wide and complex  but also heterogeneous in the theoretical plane. These dynamics of amplification and internationalization have in turn contributed to the questioning of gender as a category of analysis, as it had been conceptualized and fixed in occidental academic historiography.